Seagrass wasting disease prevalence and lesion area increase with invertebrate grazing across the northeastern Pacific - Lillian R. Aoki; Carmen J. Ritter; Deanna S. Beatty; Lia K. Domke; Ginny L. Eckert; Olivia J. Graham; Carla P. Gomes; Collin Gross; Timothy L. Hawthorne; Eliza Heery; Margot Hessing‐Lewis; Kevin Hovel; et al. (Ecology, 2025)
Disease is a key driver of community and ecosystem structure, especially when it strikes foundation species. In the widespread marine foundation species eelgrass ( Zostera marina ), outbreaks of wasting disease have caused large‐scale meadow collapse in the past, and the causative pathogen, Labyrinthula zosterae , is commonly found in meadows globally. Research to date has mainly focused on abiotic environmental drivers of seagrass wasting disease, but there is strong evidence from other systems that biotic interactions such as herbivory can facilitate plant diseases. How biotic interactions influence seagrass wasting disease in the field is unknown but is potentially important for understanding dynamics of this globally valuable and declining habitat. Here, we investigated links between epifaunal grazers and seagrass wasting disease using a latitudinal field study across 32 eelgrass meadows distributed from southeastern Alaska to southern California. From 2019 to 2021, we conducted annual surveys to assess eelgrass shoot density, morphology, epifauna community, and the prevalence and lesion area of wasting disease infections. We integrated field data with satellite measurements of sea surface temperature and used structural equation modeling to test the magnitude and direction of possible drivers of wasting disease. Our results show that grazing by small invertebrates was associated with a 29% increase in prevalence of wasting disease infections and that both the prevalence and lesion area of disease increased with total epifauna abundances. Furthermore, these relationships differed among taxa; disease levels increased with snail ( Lacuna spp.) and idoteid isopod abundances but were not related to abundance of ampithoid amphipods. This field study across 23° of latitude suggests a prominent role for invertebrate consumers in facilitating disease outbreaks with potentially large impacts on coastal seagrass ecosystems.

Mechanochemical degradation of per- and polyfluoroalkyl substances in soil using an industrial-scale horizontal ball mill with comparisons of key operational metrics - Nicholas Battye; David Patch; Iris Koch; Ryan Monteith; Dylan Roberts; Natalia O'Connor; Bernard Kueper; Michael Hulley; Kela Weber (Science of The Total Environment, 2024)

Disease surveillance by artificial intelligence links eelgrass wasting disease to ocean warming across latitudes - Lillian R. Aoki; Brendan Rappazzo; Deanna S. Beatty; Lia K. Domke; Ginny L. Eckert; Morgan E. Eisenlord; Olivia J. Graham; Leah Harper; Timothy L. Hawthorne; Margot Hessing‐Lewis; Kevin A. Hovel; Zachary L. Monteith; et al. (Limnology and Oceanography, 2022)
Ocean warming endangers coastal ecosystems through increased risk of infectious disease, yet detection, surveillance, and forecasting of marine diseases remain limited. Eelgrass ( Zostera marina ) meadows provide essential coastal habitat and are vulnerable to a temperature‐sensitive wasting disease caused by the protist Labyrinthula zosterae . We assessed wasting disease sensitivity to warming temperatures across a 3500 km study range by combining long‐term satellite remote sensing of ocean temperature with field surveys from 32 meadows along the Pacific coast of North America in 2019. Between 11% and 99% of plants were infected in individual meadows, with up to 35% of plant tissue damaged. Disease prevalence was 3× higher in locations with warm temperature anomalies in summer, indicating that the risk of wasting disease will increase with climate warming throughout the geographic range for eelgrass. Large‐scale surveys were made possible for the first time by the Eelgrass Lesion Image Segmentation Application, an artificial intelligence (AI) system that quantifies eelgrass wasting disease 5000× faster and with comparable accuracy to a human expert. This study highlights the value of AI in marine biological observing specifically for detecting widespread climate‐driven disease outbreaks.

Mule deer and energy development—Long‐term trends of habituation and abundance - Hall Sawyer; Nicole M. Korfanta; Ryan M. Nielson; Kevin L. Monteith; Dale Strickland (Global Change Biology, 2017)
As the extent and intensity of energy development in North America increases, so do disturbances to wildlife and the habitats they rely upon. Impacts to mule deer are of particular concern because some of the largest gas fields in the USA overlap critical winter ranges. Short‐term studies of 2–3 years have shown that mule deer and other ungulates avoid energy infrastructure; however, there remains a common perception that ungulates habituate to energy development, and thus, the potential for a demographic effect is low. We used telemetry data from 187 individual deer across a 17‐year period, including 2 years predevelopment and 15 years during development, to determine whether mule deer habituated to natural gas development and if their response to disturbance varied with winter severity. Concurrently, we measured abundance of mule deer to indirectly link behavior with demography. Mule deer consistently avoided energy infrastructure through the 15‐year period of development and used habitats that were an average of 913 m further from well pads compared with predevelopment patterns of habitat use. Even during the last 3 years of study, when most wells were in production and reclamation efforts underway, mule deer remained >1 km away from well pads. The magnitude of avoidance behavior, however, was mediated by winter severity, where aversion to well pads decreased as winter severity increased. Mule deer abundance declined by 36% during the development period, despite aggressive onsite mitigation efforts (e.g. directional drilling and liquid gathering systems) and a 45% reduction in deer harvest. Our results indicate behavioral effects of energy development on mule deer are long term and may affect population abundance by displacing animals and thereby functionally reducing the amount of available habitat.

Linking habitat selection to fitness-related traits in herbivores: the role of the energy landscape - Ryan A. Long; R. T. Bowyer; Warren P. Porter; Paul Mathewson; Kevin L. Monteith; Scott L. Findholt; Brian L. Dick; John G. Kie (Oecologia, 2016)